白令海夏季浮游细菌和原生动物生物量及分布特征 - 何剑锋; 陈波; 曾胤新; KANGS-H; 王桂忠 (2005)
1999年7月21日至8月1日在我国首次北极科学考察期间,考察了白令海中部的浮游细菌和原生动物,分析了其丰度、分布、生物量及其生态作用,结果显示,浮游细菌表层生物量为1.5～20.2μg/dm3,平均为浮游植物生物量的30%,100m以上水柱柱总生物量(720～3123mg/m2)平均为浮游植物柱总生物量的67%,因而是白令海夏季与浮游植物处同等量级的优势类群;原生动物表层生物量为1.2～27.4μg/dm3,100m以上水柱柱总生物量为189～1698mg/m2,平均为浮游植物柱总生物量的21%,其中粒径小于5,5～20μm和大于20μm的原生动物分别占其柱总生物量的13%,47%和40%;作为主要类群的异养腰鞭毛虫占原生动物柱总生物量的39%.浮游细菌和原生动物生物量的总体分布趋势从西部向东北和东部递减、从表层向深层衰减,20～25m水层温跃层和表层海流的存在对这一分布特性可能有较大的影响.原生动物受潜在的大、中型浮游动物捕食压力的制约,维持了一个相对较低的生物量水平,在一定程度上限制了微食物环(microbial foodloop)在该海域夏季生态系统营养中的作用. The abundance, biomass and distribution characteristics of bacteria and protozoa and their ecological role in the planktonic community of the Bering Sea were investigated between 21 July and 1 August 1999. Bacterial carbon biomass in the surface waters ranges from 1.5 to 20.2 μg/dm~3, which accounts for 30% of phytoplankton biomass on average. The biomass of bacteria integrated over the depth from 0 to 100 m of the water column varies from 720 to 3123 mg/m~2 and accounts for 67% of the total phytoplankton biomass. The biomass of protozoa ranges from 1.2 to 27.4 μg/dm~3 in the surface layers, and varies from 189 to 1698 mg/m~2 in the upper 100 m of the water column, which constitutes 21% of integrated biomass of phytoplankton. The integrated biomass of protozoa in being less than 5 μm, 5~20 μm and being greater than 20 μm size fractions accounts for 13%, 47% and 40% of the total biomass, respectively. As a main protozoan assemblage, the integrated biomass of dinoflagellates constituts 39% of the total biomass of protozoa. The biomass of bacteria and protozoa decreases from western to northeastern and eastern regions of the Bering Sea, and the biomass of these organisms also decreases with depth. Such distribution characteristics might be influenced by both the thermocline observed at a depth from 20 to 25 m and the water current existed in the surface layers in the investigation area. The great biomass of macrozooplankton in the investigation area suggests that it might be an important cause for the lower relative biomass of protozoa, which limits the role of the microbial loop in the Bering Sea in summer. 国家自然科学基金资助项目(40006010,30270112);; 科技部基础数据(2003DEB5J057)资助项目.